The Politics of Deuteronomy - Samuel, Harald; Arnold, Bill T. (Mohr Siebeck, 2025)
The Book of Deuteronomy served as a kind of constitution for ancient Israel and later Judaism. The so-called Law of Offices, a passage at its center (Deut. 16:18-18:22), defines the roles of judges, kings, priests, and prophets. The essays in this book consider the significance of the text for todays theologians, political theorists, and legal scholars.
PublicationDate: 20250320
Keywords: Theology -- Deuteronomy -- Covenant -- Exempla -- machine learning -- democracy -- market design -- constitutional law -- Altes Testament -- Praktische Theologie -- Antike -- Rechtsgeschichte -- Religion und Recht